Characterization of midgut microbiome of Anopheles stephensi Liston - Minisha Heracl Pereira; Ajeet Kumar Mohanty; Sandeep Garg; Suchi Tyagi; Ashwani Kumar (Journal of Vector Borne Diseases, 2021)
Background & objectives: Anopheles stephensi is an important vector of malaria in South East Asia. The abundance and diversity of gut microbiota in the disease vectors affect their development, digestion, metabolism and immunity. The immatures of An. stephensi engulf microbes from their aquatic environment. The present study investigates midgut microbiota of wild and laboratory populations and compares it with their habitat bacterial diversity to study transstadial transmissibility. Methods: The gut microbes from immatures, adults and water samples were cultured at ambient conditions on different media. The colony and biochemical characteristics, and 16S rRNA gene sequencing of gut microbes were studied. Results: Altogether, 298 bacterial isolates were characterized as 21 genera belonging to four major Phyla viz., Actinobacteria, Bacteroidetes, Firmicutes and Proteobacteria. In the field population-1, Proteobacteria and Firmicutes accounted for 49% and Actinobacteria constituted 51% of the bacterial isolates. In field population-2, Bacteroidetes and Firmicutes accounted for 99% of the isolates. In the laboratory populations, Firmicutes constituted 77%, while Proteobacteria 23% of the isolates. Additionally, 9 genera occurred in the breeding habitats, 13 in the larval midgut, 6 in pupal midgut, 9 in male midgut and 10 in the female midgut. Interpretation & conclusion: This is a unique study on diversity of microbiota of An. stephensi from breeding water, developmental stages and adults. Different culture media used enhanced the isolation of diverse bacteria. The presence of Micrococcus and Leucobacter in different life stages indicates their adaptation in An. stephensi as symbionts which need further evaluation for their role in paratransgenesis.